Housing and psychosocial factors associated with mental health in children aged 6–12 years from homeless families in the Greater Paris area, France: the ENFAMS cross-sectional study - Estevez, Mégane; Oppenchaim, Nicolas; Descarpentrie, Alexandra; Rambliere, Lison; Douay, Caroline; Galera, Cédric; Vandentorren, Stéphanie (Frontiers in Child and Adolescent Psychiatry, 2023)
Objective This study aimed to identify the housing and psychosocial factors associated with mental health disorders in children aged 6–12 years living in sheltered homeless families in the Greater Paris area (France), with a view to guiding the development of actions that could improve their mental health. Method The cross-sectional study ENFAMS (“Enfants et familles sans logement”) was conducted between January and May 2013 on a random sample of sheltered homeless families in the Greater Paris area using face-to-face questionnaires administered by trained interviewers and psychologists in 17 languages. The questionnaires collected data on socio-demographics, living conditions, and health characteristics for the child and one of the parent selected. Mental health disorders were assessed in 198 children using the Dominic Interactive tool. Statistical analyses were performed using multiple linear regression on complete data. Results The Dominic Interactive mean score was 28.8 (SD = 17.5), and it showed that 25.3% of the children had a possible or probable mental health disorder. Factors associated with higher children total difficulties scores, as measured by the Dominic Interactive, were parents' irregular administrative status, the child sleeping in the parents' bed, the child having been hospitalized in the past 12 months, and the child being bullied at school. Conclusion Our findings highlight the importance of psychosocial determinants in children's mental health, and underline the need for prevention actions for homeless families which focus on improving living, schooling, and healthcare conditions, especially greater access to mental health care.